START STRONG SCHOOL PREPARATION MODEL (SSSPM): MODEL PERSIAPAN TAHUN AJARAN BERBASIS ORGANISASI, KURIKULUM, MUTU, DAN PENGEMBANGAN SUMBER DAYA MANUSIA DI SEKOLAH ISLAM di PPIA BAITUL MAAL - Maya Yunus (STKIP Pesisir Selatan, 2026)
Most educational institutions still view preparations for the start of the school year as merely administrative routines, such as developing teaching materials and assigning tasks. This approach risks leading to unprepared teachers and poor coordination between departments. This study aims to analyze the implementation of strategies for preparing for the new school year at PPIA Baitul Maal and to formulate a robust conceptual management model for Islamic schools. Using a qualitative approach with a case study design, data collection was conducted from April to July 2025 through participatory observation, analysis of institutional documents, and in-depth interviews involving 9 key informants ranging from strategic leadership to educational staff. Data analysis applied the interactive model Miles, Huberman, and Saldaña, whose validity was validated through triangulation. The research findings revealed that preparations were executed in a structured manner through five essential stages: organizational structuring, curriculum development, strengthening quality assurance, scaling up human resource capacity, and operational finalization. These findings led to the formulation of the Start Strong School Preparation Model. As a concrete recommendation, educational institution leaders are advised to adopt the SSSPM into their Annual Work Plan cycle to mitigate managerial inefficiencies and build a sustainable quality ecosystem before academic year begins.